PLAN ESTRATÉGICO DE MARKETING 2020-2025 PARA EL HOTEL VILCABAMBA EN LA CIUDAD DE LOJA - González Guachizaca, Daniela Catalina (2021)
The general objective for the development of this thesis work is: “To prepare a Strategic Marketing Plan for the Hotel Vilcabamba, in the city of Loja”, a very important tool for the company, in achieving its business objectives and goals that are in accordance with its vision and mission, achieving the strengthening of its organization, identifying internal-external aspects, through the use of the SWOT. Methods and techniques were used that served as a guide in carrying out this work: historical, deductive, inductive, statistical, scientific, and analytical method. As techniques were present: The bibliographic, direct observation, the interview applied to the Manager, and finally the survey technique was applied, used for the 11 employees, and 334 customers and 16 regular customers of the hotel. These data collaborated to formulate the strengths, opportunities, weaknesses and threats, with the support of field research for the design of the SWOT matrix. Subsequently, the company's situational diagnosis was prepared taking into account the external analysis, which determined: economic and financial, social, cultural, demographic, technological, scientific, ecological and environmental forces, in addition to analyzing the environment by Porter's five forces: Bargaining power with clients, with suppliers, potential entry of new consumers, potential development of substitute services, rivalry between competing companies; analysis of opportunities and threats. Likewise, the internal analysis was carried out as the commercial organization and the service, the analysis of the environment through the diagnosis through surveys 5 submitted to the internal and external client, in addition, the marketing mix study and the strengths and weaknesses were developed. Finally, the development axes were defined, the strategic objectives, to which strategies with their respective activities, tactics, and policies were incorporated, taking into account the following parameters: comprehensive marketing management model (capture systems, sustainability, recovery, growth and referencing of clients, loyalty programs and return to society system), operational projects (preparation of the functions manual, improving coverage channels to increase market share, advertising plan in print and radio media, induction manual for facilitate the adaptation and integration of the new worker), marketing mix (product, price, place, promotion) and SWOT analysis (weaknesses), with which the strategic marketing plan for the Vilcabamba hotel was concluded. Finally, the conclusions and recommendations were determined based on the results and discussion of the research project.